Endoscopic surgery for thalamic hemorrhage breaking into ventricles: Comparison of endoscopic surgery, minimally invasive hematoma puncture, and external ventricular drainage - Fu, Chu-Hua (Chin J Traumatol, 2019)
PURPOSE: Thalamic hemorrhage breaking into ventricles (THBIV) is a devastating disease with high morbidity and mortality rates. Endoscopic surgery (ES) may improve outcomes, although there is no consensus on its superiority. We investigated the efficacy and safety of ES and compared the outcomes of different management strategies by ES, hematoma puncture and drainage (HPD), and external ventricular drainage (EVD) in patients with THBIV. METHODS: We retrospectively analyzed patients with THBIV treated by ES, HPD, or EVD at our hospital from June 2015 to June 2018. Patients were categorized into anteromedial and posterolateral groups based on THBIV location, and then the two groups were further divided into ES, HPD, and EVD subgroups. Individualized surgical approach was adopted according to the location of the hematoma in the ES subgroups. Patient characteristics and surgical outcomes were investigated. RESULTS: We analyzed 211 consecutive patients. There were no significant differences in clinical characteristics or incidence of perioperative procedure-related complications (postoperative rebleeding and intracranial infection) in either anteromedial or posterolateral groups. Compared with other therapeutic methods, the ES subgroups had the highest hematoma evacuation rate, shortest drainage time, and lowest incidence of chronic ventricular dilatation (all p < 0.05). Among the three anteromedial subgroups, ES subgroup had the best clinical outcomes which was assessed by the modified Rankin Scale, followed by HPD and EVD subgroups (p < 0.01); while in the posterolateral subgroups, clinical outcomes in the ES and HPD subgroups were similar and better than that in the EVD subgroup (p = 0.037). CONCLUSION: Individualized surgical ES approach for removal of thalamic and ventricular hematomas is a minimally invasive, safe, and effective strategy for the treatment of THBIV with a thalamic hematoma volume of 10–30 mL.